Stereotype Susceptibility in Children: Effects of Identity Activation on Quantitative Performance - Ambady, Nalini; Shih, Margaret; Kim, Amy; Pittinsky, Todd L. (Psychological Science, 2001)
A growing body of research indicates that the activation of negative stereotypes can impede cognitive performance in adults, whereas positive stereotypes can facilitate cognitive performance. In two studies, we examined the effects of positive and negative stereotypes on the cognitive performance of children in three age groups: lower elementary school, upper elementary school, and middle school. Very young children in the lower elementary grades (kindergarten-grade 2) and older children in the middle school grades (grades 6–8) showed shifts in performance associated with the activation of positive and negative stereotypes; these shifts were consistent with patterns previously reported for adults. The subtle activation of negative stereotypes significantly impeded performance, whereas the subtle activation of positive stereotypes significantly facilitated performance. Markedly different effects were found for children in the upper elementary grades (grades 3–5). These results suggest that the development of stereotype susceptibility is a critical domain for understanding the connection between stereotypes and individual behavior.